Eating Disorders and Type 1 Diabetes: A Perspective - Marucci, Simonetta; De Iaco, Giulia; Lisco, Giuseppe; Mariano, Francesco; Giagulli, Vito A.; Guastamacchia, Edoardo; De Pergola, Giovanni; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Patients with type 1 diabetes (T1D) are at risk of clinical eating disorders (EDs) and disordered eating behaviors (DEBs) than the general population. This burden is related mainly to diabetes-related physical and psychosocial issues especially beginning during childhood. DEBs must be investigated carefully and promptly managed in case of suspicion, as they can evolve into severe clinical EDs over time and are strictly related to poor outcomes. The significant number of scientific articles dealing with the relationship between T1D and DEBs or EDs confirms the complexity of these problems and the difficulties in diagnosis and treatment. This paper examined current scientific literature related to this topic, emphasizing the epidemiological and clinical complexity of the phenomenon and briefly summarizing EDBs management strategy in T1D patients.
Keywords: anorexia nervosa